Experimental and theoretical analysis of exhaust manifold by uncoated and coated ceramics (Al2O3, TiO2 and ZrO2) - Kumar, K. Sunil; Kalos, Pritam Suryaprakash; Akhtar, Mohammad Nishat; Shaik, Saboor; Sundara, Vikram; Fayaz, H.; Khan, Sher Afghan; Asif, Mohammad (Elsevier, 2023)
This research work focuses on the experimental and theoretical analysis of the exhaust manifold with novel ceramic coatings(TiO2 Coatings; ZrO2 coatings; and Al2O3 coatings) and these coatings were applied on the manifold by the plasma arc technique with a temperature range of 14000 degrees C and micron coatings ranging from 350-400µ. Implementing these coatings over the exhaust manifold gives enormous benefits such as improvised endurance strength, higher heat dissipation, and flexible directional heat flux compared to uncoated materials. The numerical analysis found that the ceramic coatings give lower thermal residual stresses compared to the uncoated materials. Among the three coatings, Al2O3 coatings give optimal performance in terms of heat dissipation, heat flux, directional heat flux, and lower thermal residual stresses. From the overall analysis; it is also clear that the implementation of ceramic coatings on the exhaust manifold gives enormous advantages in terms of corrosion resistance and lesser maintenance as compared to uncoated materials.